DISCHARGING ACCOUNTABILITY: A CASE STUDY OF A ZAKAT INSTITUTION IN MALAYSIA - Norfaiezah Sawandi; Norazita Marina Abdul Aziz; Ram Al Jafri Saad (International Journal of Supply Chain Management, 2019)
The objective of the study is to explore and examine the forms and means employed by one zakat institution in Malaysia in discharging its accountability to the stakeholders. Case study approach was used in the study involving the use of both of primary and secondary data. The primary data was gathered via the face to face in-depth interviews that were conducted with the representatives of the zakat institution. The secondary data was gathered from different sources such as the zakat collection and distributions reports of the zakat institution. The interview data was analysed using a manual coding and the secondary data was content analysed using a thematic analysis. The study finds that the zakat institution studied has been discharging two categories of accountability that are financial or formal and social or informal form of accountability. The financial/formal form of accountability has been discharged mainly via the zakat collection and distribution reports. Meanwhile, it is observed that the latter category of accountability has been discharged through both of means that are account- and action-based mechanisms, which include zakat collection and distribution reports and various non-zakat society/community programs respectively.